INDONESIA AND CENTRAL ASIA: ROMANTICIZING AUTHORITARIAN REGIME IN THE PAST? - Aviandy, Mochamad (UI Scholars Hub, 2019)
Even though countries in Central Asia and Indonesia seem to be unrelated, both actually have experienced authoritarian regime and implemented decentralization system after that regime collapsed. Nevertheless, decentralization along with non-authoritarian regime does not automatically bring the desired good result since a new authoritarian regime based on decentralization appears. As a result, the citizens long for the welfare of the centralism system. Before talking further about the comparison of both regions, it is better to have a good understanding of each region.